Media-equipment in households 1977 - Radio Sweden (Radio Sweden, 1984)
This survey forms part of the project ´Massmedieutveckling under 80-talet´. For each kind of equipment the respondent was asked about number of devices, year of purchase and money spent on buying the equipment. Other questions dealt with possession of records and cassettes, type of music on records and cassettes, purchases during 1976 and amount of different kinds of music played each week. Furthermore the respondent was asked about subscription to different newspapers, purchases of single copies and amount of time spent reading newspapers.

Purpose:

Show which media equipment exists in the Swedish households

Denna undersökning är en del av projektet "Massmedieutveckling i 80-talet". För varje typ av beskriven utrustning har respondenten tillfrågats om antalet enheter, vilket år den inköpts och hur mycket den kostat. Andra frågor behandlade innehav av skivor och kassetter, typ av musik på skivor och kassetter, inköp under 1976 och hur mycket man lyssnar på olika typer av musik under en vecka. Dessutom ställdes frågor om prenumeration på olika tidningar, köp av enstaka nummer och tid ägnad åt att läsa tidningar.

Syfte:

Visa vilken mediautrustning som finns i de svenska hushållen

Den version som överlämnats till SSD innehåller 2.914 individer, varav 6 st. måst uteslutas på grund av maskinläsfel. Den tillrättalagda versionen omfattar således 2.908 individer eller 68,9% av nettourvalet.
Apparatbestånd på mediesidan i hemmen 1977
Keywords: consumption; konsumtion; newspaper readership; tidnings läsekrets; listening to music; musiklyssnande; audio equipment; ljudutrustning; television; television; radio; radio; cinema attendance; biobesök; music; musik; purchasing; köp; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Social Sciences; Samhällsvetenskap